2018
DOI: 10.1177/1024907918806641
|View full text |Cite
|
Sign up to set email alerts
|

Utility of neutrophil gelatinase-associated lipocalin in the management of acute kidney injury: A prospective, observational study

Abstract: Background: Utilization of renal biomarkers such as neutrophil gelatinase-associated lipocalin in the management of acute kidney injury may be useful as a diagnostic tool in the emergency department. Objective: The aim of this study is to determine the relationship between serum neutrophil gelatinase-associated lipocalin level and the severity of the acute kidney injury based on the Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease (RIFLE) classification, and to investigate the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Nevertheless, this study has demonstrated the possible utility of raised CRP levels and the usefulness of early intervention by initiating antibiotic treatment in the ED, with a potentially positive effect on reduction of hospital LoS. Future studies could investigate the role of CRP further and explore the utility of other potential biomarkers for renal disease 25 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, this study has demonstrated the possible utility of raised CRP levels and the usefulness of early intervention by initiating antibiotic treatment in the ED, with a potentially positive effect on reduction of hospital LoS. Future studies could investigate the role of CRP further and explore the utility of other potential biomarkers for renal disease 25 …”
Section: Discussionmentioning
confidence: 82%
“…Future studies could investigate the role of CRP further and explore the utility of other potential biomarkers for renal disease. 25…”
Section: Discussionmentioning
confidence: 99%